Co‐producing research with youth: The NeurOx young people's advisory group model. (16th May 2019) - Pavarini, Gabriela; Lorimer, Jessica; Manzini, Arianna; Goundrey‐Smith, Ed; Singh, Ilina
Abstract: Context: The 1989 UN Convention on the Rights of the Child states that children have the right to be heard in all matters affecting them. The Convention inspired a surge in research that investigates young people's perspectives on health and wellness‐related concerns and that involves children as 'co‐researchers'. Young people's advisory groups (YPAGs) are a widely used method to enable young people's involvement in all research stages, but there is a lack of academic literature to guide researchers on how to set up, run and evaluate the impact of such groups. Objective: In this paper, we provide a step‐by‐step model, grounded in our own experience of setting up and coordinating the Oxford Neuroscience, Ethics and Society Young People's Advisory Group (NeurOx YPAG). This group supports studies at the intersection of ethics, mental health and novel technologies. Our model covers the following stages: deciding on the fit for co‐production, recruiting participants, developing collective principles of work, running a meeting and evaluating impact. Results: We emphasize that throughout this process, researchers should take a critical stance by reflecting on whether a co‐production model fits their research scope and aims; ensuring (or aspiring to) representativeness within the group; valuing different kinds of expertise; and undertaking on‐going evaluations on the impact of the group on both the young people and the research. Conclusion: Adopting a critical and reflective attitude can increase researchers' capacity to engage youth in democratic and inclusive ways, and to produce research outputs that are aligned with the target audience's needs and priorities.